Propuesta de un sistema integral para el manejo de residuos sólidos industriales peligrosos en la ciudad de Trujillo - Flores Barbarán, Manuel Agustín (2011)
We have implemented an Integrated Management Plan Hazardous Industrial Solid Waste generated by industries in the city of Trujillo, which includes lines of action, and sub for each social group directly involved in joint solutions to find optimal solutions in the management of waste. A characterization of these wastes, according to national and international standards, determining its amount considering they come from tanneries, gas stations and power generating companies, thus allowing recommending the construction of a waste treatment plant hazardous industrial solid in the city of Trujillo, to rank actions aimed at the prevention, minimization and recovery of the consequences that could result in contaminated water, soil and air, and the deterioration of ecosystems.